The financial rights of shareholders in the company : comparative study between Malaysia and Australia - Salih, Mohammed L. (Ahmab Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2010)
This study focuses on the rights of shareholders in a company in Malaysia and Australia. The primary concern of this research is the shareholders' financial rights in the company. Therefore, this research hypothesizes that Australian Corporations Act 2001 treats shareholders' financial rights in a manner which is more effective than Malaysian Companies Act 1965. The objective of this study is to ascertain the instances where the financial rights of the shareholders in the company have been prejudiced or discriminated by the directors or majority shareholders and how their financial rights are protected. The conducted research has used a comparative, analysis, and descriptive methods in order to highlight the strong and weak mechanisms that exist in the two jurisdictions, Malaysia and Australia which help to protect the financial rights of the shareholders in the company. Accordingly, the researcher found that Australian Corporations Act 2001 treats the problem mentioned above in more effective way than Malaysian Companies Act 1965. Australian Corporations Act 2001 gives company's shareholders a wide discretion to vary the right attaching to their shares, while Malaysian Companies Act 1965 does not give the company shareholders the same discretion that conferred to company's shareholders in Australia. In addition, Australian Corporations Act 2001 depends on the solvency test in declaring dividend, while the capital maintenance approach is still retained in Malaysia. Moreover, the statutory provision in Australians Corporation Act 2001 relating to the remedies and people who have locus standi to sue the wrongdoer is much clearer in comparison to Malaysian Companies Act 1965.